The Water Chemistry Geothermal of Ranang-Kasimbar Hot Springs, Parigi Moutong Regency, Central Sulawesi, Indonesia - Anna Yushantarti; Dudi Hermawan; Dwi Fitri Yudiantoro (UIR PRESS, 2026)
The Ranang-Kasimbar geothermal system in Central Sulawesi is located within the West Sulawesi Mandala, an area significantly influenced by the active tectonic zone of the Palu-Koro Fault that controls the emergence of surface manifestations. This study aims to characterize the water chemistry of the Ranang-Kasimbar hot springs through surface geological mapping and fluid geochemical analysis, which includes cation-anion analysis, stable 18O and 2H (D) isotopes, and geothermometer calculations for subsurface temperature estimation. The geological conditions of the study area are composed of Cretaceous-Eocene metamorphic rocks, Tertiary intrusive rocks, and Quaternary sedimentary rocks, with structural controls in the form of north-south trending strike-slip faults and a normal fault system that forms a central depression zone as controls for the emergence of manifestations. Field data identified hot springs with surface temperatures ranging from 55–61°C and alkaline pH ( 9). Geochemical analysis results classify the geothermal fluid as a chloride type indicating a deep reservoir origin, with a Cl/B ratio indicating strong interaction with igneous rocks and partial equilibrium conditions. Isotope analysis indicates a dominant mixing with meteoric water with very low oxygen-18 enrichment. Reservoir temperature estimation using a Na-K geothermometer and a silica-enthalpy mixing model indicates a minimum temperature of 130°C, thus categorizing it as a medium enthalpy system. This geothermal system is controlled by secondary permeability from normal and strike-slip fault structures, with the heat source suspected to originate from residual heat from Plio-Pleistocene andesitic intrusions.